Deep ecology and world religions : new essays on sacred grounds - Barnhill, David Landis; Gottlieb, Roger S. (SUNY series in radical social and political theory., 2001)
Developing from a session on deep ecology and world religions at the 1997 national meeting of the American Academy of Religion, this volume presents 12 contributions by professors of philosophy, justice studies, religion, theology, East Asian studies, and other fields. Contributions discuss deep ecology and its relationship to indigenous traditions, Hinduism, Huayan Buddhism, Daoism, Confucianism, Judaism, Catholicism, Islam, Protestantism, ecofeminism, the bible, and Ken Wilber's critique of ecological spirituality. Annotation copyrighted by Book News Inc., Portland, OR.